Geomorphologic factors affecting intrinsic vulnerability in fissured media, application on Falatados - Livada area, SE Tinos Island (Cyclades - Greece). - Leonidopoulou, D.; Evelpidou, N.; Vassilopoulos, A.; Stournaras, G. (8th International Hydrogeological Congress of Greece, 2008)
The increasing worldwide apprehension of groundwater contamination problems generated the concept of groundwater vulnerability, which is based on the theory that the natural environment can offer some degree of protection to groundwater, against the natural and human impacts, especially considering, contaminants entering the subsurface environment. Although there are several methods related to the vulnerability risk assessment and mapping for porous and karstic media, there is no relative method concerning the discontinuous media. Studying groundwater vulnerability on the smaller islands of the Aegean Sea is important, because water supplies are few and avoiding contaminants entering the groundwater is vital. Tinos Island has significant water tables, as far as quantity and quality is concerned. The selected study area is the Falatados-Livada drainage system, which is developed along the lithological contact of granites and schists. In order to assess groundwater intrinsic vulnerability, a number of effective factors were used. These factors were used as input variables of the risk model, from which derived the output variable that lead to the production of the groundwater intrinsic vulnerability risk map.